Perfusion Assessment with the SPY System after Arterial Venous Reversal for Upper Extremity Ischemia - Brooks, Darrell (Plast Reconstr Surg Glob Open, 2014)
BACKGROUND: The timing and pattern of reperfusion following arterial- venous reversal (AVR) in patients with terminal ischemia of an upper extremity is not well understood. METHODS: The current case series describes the timing and pattern of reperfusion observed in patients with terminal upper extremity ischemia who underwent AVR and repeated postoperative indocyanine green (ICG) angiography between 2004 and 2009. For all included patients, the SPY Near-Infrared Perfusion Assessment System permitted visualization of ICG-labeled blood flow for 60-second sampling periods at scheduled postoperative time points; outflow and rate and amplitude of inflow were objectively quantified with SPY-Q Analysis Toolkit image analysis software. RESULTS: The series comprised 6 male patients (mean age, 46 years) who presented with upper extremity ischemia related to hypothenar hammer syndrome (n = 2), embolism with patent foramen ovale (n = 2), atherosclerosis (n = 1), and avulsion amputation of the thumb (n = 1); the patient with the avulsion amputation was diagnosed with thromboangiitis obliterans at the time of replantation. AVR was successful in all 6 patients. In 5 of 6 patients, ICG angiography and SPY-based visualization/quantification showed that venous outflow and arterial inflow gradually normalized (versus unaffected digits) between postoperative days (PODs) 0 and 3 and was maintained at long-term follow-up (≥3 months); for the patient who underwent thumb replantation, perfusion normalized between POD 3 and month 5 follow-up. CONCLUSIONS: AVR effectively reestablished blood flow in patients with terminal upper extremity ischemia. ICG angiography with SPY technology revealed that, in most cases, kinetic curves, timing, and patterns of perfusion gradually normalized over several PODs.